Practice, Substance, and History: Reframing Institutional Logics - Mutch, Alistair (Academy of Management Review, 2018)
Roger Friedland’s characterization of institutional logics as a combination of substance and practices opens the door to a more complex reading of their influence on organizational life. His focus suggests attention to feelings and belief as much as cognition and choice. In this article I use history to develop these ideas by paying attention to the perennial features of our embodied relations with the world and other persons. Historical work draws our attention to neglected domains of social life, such as play, which can have profound impacts on organizations. The study of history suggests that such institutions have a long-run conditioning influence that calls into question accounts that stress individual agential choice and action in bringing about change. Analytical narratives of the emergence of practices can provide the means to combine the conceptual apparatus of organization theory with the attention to temporality of history.